Gestão da mudança em processos internos: um estudo em empresa de engenharia de pavimentação e construção de estradas - Pereira, Paula Ulysséa (Universidade do Vale do Rio dos Sinos, 2019)
With the constant improvement that companies had along their market trajectory, their processes undergo significant changes so that their target audience is more and more satisfied with the products and / or services offered. The need arises, therefore, for these companies to adapt to the market and to improve their processes, generating changes in the organizations that inevitably affect all those involved. Given this fact, the objective of this study is to identify employees' perception of changes in work and their influence on productivity. Through face-to-face interviews with the managers and subordinates of the administrative area of a company in the segment of paving and road construction, sought the best understanding as the changes happen. From the answers and suggestions obtained in the interviews, which resulted in a textual analysis, it was noticed that there are points to be improved in the management related communication to subordinates and barriers, creation of incentive goals and situations of resistance.
Keywords: Gestão da mudança; Gestão de pessoas; People management; Change management